The neo-liberalization of feminism within the cultural industry: Rosalía’s logical structure as an icon of the feminist movement - Vega Durán, Samuel; Samaniego Espinosa, Joaquina (Comunicación y Género [Communication and Gender], 2021)
The main aim of this work is to analyse the feminism’s logical structure within the cultural industry through Rosalía. The Critical Discourse Analysis allows the identification of the essential features of this obstructed feminism and the way in which it is linked with the values of the dominant culture. This analysis demonstrates the biased presentation of the concept of feminism and its deep connection with some ideas that support neoliberal ideology such as individualism or meritocracy.